Aluminum alloy material and aluminum alloy clad material
Patent Information
- Application Number
- JP2023137249
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-25
- Publication Date
- 2025-03-07
AI Technical Summary
【0026】 すなわち、本発明によれば、優れた耐食性を発揮し、厳しい腐食環境にも耐えることができる。
Smart Images

Figure 2025031195000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an aluminum alloy material and an aluminum alloy clad material that exhibit excellent corrosion resistance. [Background technology]
[0002] Aluminum is known as a metal with relatively high corrosion resistance. However, when it comes into contact with solutions containing halogen ions such as chlorine, or is exposed to a corrosive environment in which water droplets or liquid films form on the material surface, it can undergo severe localized corrosion. Therefore, the study of corrosion prevention technologies is an important issue. Conventional aluminum corrosion protection technologies that can withstand such corrosive environments include coating the material to prevent it from coming into contact with the corrosive environment, and sacrificial protection by providing a sacrificial protection layer with a relatively low potential on the surface as a laminate material. However, coating the material increases costs, and in sacrificial protection, adding a large amount of Zn to increase the sacrificial anode effect can increase the self-corrosion rate and accelerate the wear of the sacrificial anode material. In recent years, there has been a demand for thinner materials, so it is necessary to take a different approach to improve the corrosion resistance of the material itself.
[0003] As a prior example of a method for manufacturing an aluminum alloy with excellent self-corrosion resistance, an aluminum alloy with a total content of Al and Mg of 99.9% or more is known, in which the occurrence of corrosion can be suppressed by the MgO present on the material surface (for example, Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2006-37137 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, in the above-mentioned prior art, an aluminum alloy with a purity of 99.9% or more is used, which leads to an increase in costs, and simply generating MgO by adding Mg to the aluminum alloy does not provide sufficient corrosion resistance for use as an aluminum alloy material for heat exchangers exposed to severe corrosive environments.
[0006] The present invention has been made against the background described above, and has an object to provide an aluminum alloy material and an aluminum alloy clad material having excellent corrosion resistance that can withstand severe corrosive environments without incurring any significant increase in cost. [Means for solving the problem]
[0007] Therefore, the inventors conducted research into improving corrosion resistance and found that adding Mg and generating MgO alone was insufficient, and that corrosion resistance could be further improved by controlling the thickness of the oxide film, in which Mg has a higher atomic concentration than Al, and the generation of intermetallic compounds, etc. They also found that the thickness of the oxide film mainly composed of MgO and the state of the intermetallic compounds, etc. could be achieved by optimizing the manufacturing process (such as the heat load conditions in each process).
[0008] That is, among the aluminum alloy materials of the present invention, a first embodiment contains, by mass%, Mg: 0.5 to 2.0%, Fe: 0.3% or less, Si: 0.1 to 0.3%, and the balance is made of Al and unavoidable impurities, and has a composition in which a Si / Fe ratio, which is a ratio of the Si content to the Fe content, by mass%, is 0.5 or more, and a Mg / Si ratio, which is a ratio of the Mg content to the Si content, by mass%, is 2.0 or more; The oxide film has a higher atomic concentration of Mg than Al formed on the surface, the thickness of the oxide film is 20 nm or more, the area ratio of intermetallic compounds having an equivalent circle diameter of 0.01 μm or more is 3.0% or less when observed on the surface (RD-TD), and the abundance ratio of MgO and MgAl2O4 in the oxide film is 4.0 or more.
[0009] The invention of the aluminum alloy material of another embodiment is characterized in that, in the invention of the above embodiment, the composition further contains, by mass%, Zn: 0.1 to 2.0%, and the Mg / Zn ratio, which is the ratio of the Mg content to the Zn content, by mass%, is 0.3 or more.
[0010] The aluminum alloy material of the invention according to another aspect of the present invention is characterized in that the composition of the aluminum alloy material of the invention according to the above aspect further contains, by mass %, 0.1 to 0.3% Mn.
[0011] The invention of the aluminum alloy material of another aspect is characterized in that, in the invention of the above aspect, the inevitable impurities in the composition are restricted to Cu: 0.01% or less.
[0012] The aluminum alloy clad material of the present invention is obtained by laminating the aluminum alloy material of the above-mentioned form as a sacrificial anode material to one or both sides of a core material.
[0013] The contents stipulated in the present invention will be explained below. Composition: All the compositions below are expressed in mass %.
[0014] Mg: 0.5-2.0% Mg forms an oxide film on the material surface, in which the atomic concentration of Mg is higher than that of Al, and contributes to improving corrosion resistance. If the content is below the lower limit, the desired effect cannot be obtained, and if the content exceeds the upper limit, cracks will occur during hot rolling, making manufacturing difficult. For the same reason, it is preferable to set the lower limit at 0.8% and the upper limit at 1.5%.
[0015] Fe: 0.3% or less Fe is not actively added because it causes deterioration of corrosion resistance, but the upper limit is 0.3%. If the content exceeds the upper limit, a large amount of intermetallic compounds will be generated, causing deterioration of corrosion resistance. Furthermore, it is preferable that the content be 0.2% or less. However, since less than 0.05% will lead to an increase in costs, it is preferable that the content be 0.05% or more.
[0016] Silicon: 0.1 to 0.3% Silicon forms Al-Fe-Si compounds, which suppress the formation of Al-Fe compounds that contribute to an increase in the corrosion rate. However, if the content is less than the lower limit, the desired effect cannot be obtained, and if the content exceeds the upper limit, the formation of Mg2Si is promoted, the amount of dissolved Mg decreases, and the amount of MgO formed decreases, deteriorating the corrosion resistance. For the same reason, it is preferable to set the lower limit at 0.15% and the upper limit at 0.2%.
[0017] Si / Fe ratio: 0.5 or more The Si / Fe ratio, which is the ratio of the Si content by mass % to the Fe content by mass %, is related to the formation of Al-Fe compounds and Al-Si-Fe compounds that contribute to corrosion resistance. If the Si / Fe ratio is less than 0.5, Al-Fe compounds are formed in preference to Al-Fe-Si compounds, increasing the corrosion rate and deteriorating corrosion resistance. Therefore, the Si / Fe ratio must be 0.5 or more. For the same reason, it is desirable for the Si / Fe ratio to be 1.0 or more.
[0018] Mg / Si ratio: 2.0 or more The Mg / Si ratio, which is the ratio of the Mg content in mass% to the Si content in mass%, is related to the formation of Mg2Si. If too much Mg2Si is formed, the dissolved Mg will be depleted, inhibiting the formation of MgO and making it impossible to obtain sufficient corrosion resistance. Therefore, the Mg / Si ratio must be 2.0 or more. For the same reason, it is desirable for the Mg / Si ratio to be 3.0 or more.
[0019] The atomic concentration of Mg is higher than that of Al. The thickness of the oxide film is 20 nm or more. Oxide films with a higher atomic concentration of Mg than Al have better self-corrosion resistance than the oxide film of normal aluminum alloys, Al2O3, and the thicker the oxide film on the material surface with a higher atomic concentration of Mg than Al, the better the corrosion resistance it exhibits. However, if the film thickness is less than 20 nm, the desired effect cannot be obtained. The oxide film is mainly composed of MgO.
[0020] Observation of the surface (RD-TD) shows that the area ratio of intermetallic compounds with a circle equivalent diameter of 0.01 μm or more is 3.0% or less. Since the intermetallic compounds present on the surface may inhibit the uniform formation of an oxide film in which the atomic concentration of Mg is higher than that of Al, and may become the starting point of corrosion, thereby deteriorating the corrosion resistance, good corrosion resistance is exhibited as long as the area ratio of the intermetallic compounds present on the surface having a desired circle equivalent diameter of 0.01 μm or more is not more than this. However, if the area ratio exceeds 3.0%, the desired effect cannot be obtained.
[0021] The ratio of MgO to MgAl2O4 in the oxide film is 4.0 or more. Mg reduces and decomposes the Al oxide film (Al2O3) to produce MgAl2O4. Since the MgAl2O4 present on the surface is a defect in the oxide film and serves as the starting point for corrosion, the lower the ratio of MgO to MgAl2O4 in the oxide film, where the atomic concentration of Mg is higher than that of Al, the better the corrosion resistance. If the ratio is less than 4.0, the desired effect cannot be obtained.
[0022] Zn: 0.1-2.0% Zn is optionally contained since it has a sacrificial anticorrosive effect by making the pitting potential of the material more base than other materials. If the content is less than the lower limit, the effect is insufficient, and if the content exceeds the upper limit, the corrosion rate increases and the corrosion resistance deteriorates. For the same reason, it is preferable to set the lower limit at 0.8% and the upper limit at 1.5%. When Zn is not actively added, it may be contained as an unavoidable impurity, and may contain 0.01% or less.
[0023] Mg / Zn ratio: 0.3 or more When Zn is contained, the Mg / Zn ratio, which is the ratio of the Mg content in mass% to the Zn content in mass%, is related to the formation of MgZn2. If the Mg / Zn ratio is less than 0.3, MgZn2 is formed in excess, so that the dissolved Mg is depleted, inhibiting the formation of MgO and making it impossible to obtain sufficient corrosion resistance. Therefore, it is preferable that the Mg / Zn ratio is 0.3 or more. For the same reason, it is even more preferable that the Mg / Zn ratio is 0.5 or more.
[0024] Mn: 0.1-0.3% Mn is optionally contained because it suppresses the formation of Al-Fe compounds that contribute to an increase in the corrosion rate by forming Al-Mn-Fe and Al-Mn-Fe-Si compounds. However, if the content is less than the lower limit, the effect is insufficient, and if the content exceeds the upper limit, a large amount of intermetallic compounds is generated, deteriorating the corrosion resistance. For the same reason, it is preferable to set the lower limit at 0.15% and the upper limit at 0.25%. In addition, when Mn is not actively added, it may be contained as an inevitable impurity, and may contain 0.01% or less.
[0025] Cu: 0.01% or less Cu is not actively added because it causes deterioration of corrosion resistance. If the content exceeds the upper limit, it will cause deterioration of corrosion resistance. For the same reason, it is even more preferable that the content be 0.01% or less. Effect of the Invention
[0026] That is, according to the present invention, excellent corrosion resistance is exhibited and the material can withstand even severe corrosive environments. [Brief description of the drawings]
[0027] [Figure 1] 1 shows a cross-sectional view of an aluminum alloy clad material according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0028] An embodiment of the present invention will be described below.
[0029] When producing an aluminum alloy material as a bare material, an aluminum alloy satisfying the composition of the present invention is prepared, cast, and if necessary, homogenized, and then subjected to facing, soaking, hot rolling, and cold rolling.
[0030] casting Casting is performed, for example, by semi-continuous casting. If the cooling rate during casting is slow, the compounds crystallized during casting tend to become coarse. As a result, the desired area ratio of intermetallic compounds having an equivalent circle diameter of 0.01 μm or more cannot be obtained. Therefore, the cooling rate is desirably 0.1° C. / sec or more, more desirably 1° C. / sec or more.
[0031] Homogenization In the homogenization treatment, the obtained ingot can be subjected to homogenization treatment at 400°C or higher. Preferably, the homogenization treatment is performed at a temperature of 560°C or higher. This suppresses the generation of Mg2Si, thereby suppressing the decrease in the amount of dissolved Mg, and the desired appropriate atomic concentration of Mg is higher than that of Al, and an oxide film thickness mainly composed of MgO is obtained. Under conditions below the desired temperature, Mg2Si is more likely to be generated and the amount of dissolved Mg is reduced, making it impossible to obtain the desired appropriate atomic concentration of Mg is higher than that of Al, and an oxide film thickness thickness mainly composed of MgO is obtained. Homogenization treatment is performed for a time period ranging from 1 hour to less than 12 hours. If the treatment time is less than 1 hour, the metal structure of the resulting ingot cannot be made uniform, and if it exceeds 12 hours, there will be no change in the ingot structure, so homogenization is not necessary.
[0032] Surface cutting The facing can be performed as necessary, and the content of the facing is not particularly limited in this embodiment.
[0033] Heat treatment The soaking treatment can be performed in preparation for hot rolling, and is not limited to any particular condition in this embodiment.
[0034] Hot rolling By controlling the reduction amount per pass, the coarse intermetallic compounds formed during casting are crushed during hot rolling, and the desired area ratio of intermetallic compounds having a diameter of 0.01 μm or more in equivalent circle diameter is obtained. Specifically, it is desirable to perform a rolling pass that involves a thickness reduction of 20% or more, more preferably 30% or more per pass. If the reduction amount is less than 20%, the coarse intermetallic compounds formed during casting remain, and the area ratio of intermetallic compounds present on the surface having a diameter of 0.01 μm or more in equivalent circle diameter cannot be obtained.
[0035] Cold rolling In cold rolling, the intermetallic compounds crushed during hot rolling are crushed further into smaller pieces, so that the area ratio of intermetallic compounds present on the surface and having a diameter of 0.01 μm or more in equivalent circle diameter is obtained. Specifically, it is preferable to carry out the rolling reduction rate per pass at 20% or more, more preferably at 30% or more. Under conditions of a rolling reduction rate less than this, coarse intermetallic compounds remain, and the desired area ratio of intermetallic compounds having a diameter of 0.01 μm or more in equivalent circle diameter is not obtained.
[0036] Thereafter, intermediate and final annealing and brazing are performed as necessary, as will be described later.
[0037] Clad Material The aluminum alloy material of the present invention may be used as a bare material, but may also be used as a constituent material of a clad material in which it is clad with other materials. In producing the clad material, the aluminum alloy material of the present invention is used as a sacrificial anode material (skin material) and is subjected to casting, homogenization treatment, facing (if necessary), soaking treatment, and hot rolling. The manufacturing of clad materials involves casting the core material, homogenizing it, and machining the surface.
[0038] In clad rolling, a sacrificial anode material and a core material are assembled, and then soaked, hot rolled, cold rolled, and, if necessary, intermediate and final annealing and brazing are performed.
[0039] Hot rolling Hot rolling of clad materials involves a pressing pass for pressing the skin material and the core material together, and a rolling pass for rolling to a specified thickness. Here, only the rolling pass for rolling to a specified thickness is mentioned. By controlling the reduction amount per pass, the coarse intermetallic compounds formed during casting are crushed during hot rolling, and the area ratio of the intermetallic compounds having a desired equivalent circle diameter of 0.01 μm or more is obtained. Specifically, it is desirable to perform a rolling pass that involves a thickness reduction of 20% or more, more preferably 30% or more per pass. If the reduction amount is less than 20%, the coarse intermetallic compounds formed during casting remain, and the area ratio of the intermetallic compounds present on the surface having a desired equivalent circle diameter of 0.01 μm or more cannot be obtained.
[0040] Cold rolling As with the bare material, the intermetallic compounds crushed during hot rolling can be further crushed into smaller pieces to obtain a desired area ratio of intermetallic compounds having an equivalent circle diameter of 0.01 μm or more.
[0041] Intermediate and final annealing Both bare and clad materials can be annealed after rolling to a predetermined thickness. Annealing in an appropriate temperature range promotes the formation of an oxide film in which the atomic concentration of Mg is higher than that of Al. Specifically, annealing is performed at 250°C to 400°C for 3 to 10 hours, more preferably at 300°C to 360°C. Sufficient effects cannot be obtained under conditions below the desired temperature. Under conditions above the desired temperature, Mg and Al2O3 react to form MgAl2O4, and the desired MgO / MgAl2O4 ratio cannot be obtained in the oxide film. During annealing, the furnace is filled with DX gas to prevent discoloration due to rolling oil and explosion due to rapid oxidation reaction of rolling oil mist. By controlling the oxygen concentration, the formation of films other than MgO is suppressed. Annealing is performed at an oxygen concentration of 0.01% to 0.5%, preferably 0.1% or less. Under conditions of a desired oxygen concentration or higher, the formation of Al2O3 is promoted along with MgO, and under conditions of a lower oxygen concentration than the desired oxygen concentration, the formation of MgO is suppressed, and an oxide film mainly composed of MgO cannot be obtained with a thickness appropriate for obtaining the desired corrosion resistance. Annealing is also performed by setting the temperature of the DX gas flowing into the furnace to 5°C above the dew point. Under conditions of a temperature lower than the desired temperature, the water vapor present in the air solidifies and adheres to the material surface, causing Al2O3 to form a porous layer made of aluminum oxide hydrate (Al2O3·xH2O) with many defects, which inhibits the formation of an oxide film with a higher atomic concentration of Mg than Al, making it impossible to obtain the desired thickness.
[0042] Brazing Both bare and clad materials can be brazed as needed, and can be done by holding at 590℃ for 3 minutes or more. If exposed to a high temperature environment of 400℃ or more, MgAl2O4 will be generated and a dense MgO film will not be obtained, but if it is then held in a higher temperature environment for a certain period of time, MgO can be generated to further cover the MgAl2O4, and a dense MgO film can be formed on the material surface. If the specified time is not met, sufficient effect will not be obtained.
[0043] As shown in Fig. 1, the clad material is an aluminum alloy clad material 1 in which a sacrificial anode material 3 made of the aluminum alloy material of this embodiment is clad on a core material 2, or an aluminum alloy clad material 1A in which sacrificial anode materials 3A, 3B made of the aluminum alloy material of this embodiment are clad on a core material 2. The sacrificial anode materials 3A, 3B may have the same composition, or may have different compositions within the range of the present invention. In addition, when the sacrificial anode materials are clad on both sides of the core material, one may be the sacrificial anode material made of the aluminum alloy material of this embodiment, and the other may be made of a material other than that of the embodiment of the present invention.
[0044] In the above embodiment, the provisions of the present invention are met. The thickness of the oxide film with a higher atomic concentration of Mg than Al is 20 nm or more. original In order to achieve an oxide film thickness of 20 nm or more, in which the molecular concentration of Mg is higher than that of Al, this can be achieved by adding Mg and other elements in an appropriate balance and by appropriately adjusting the conditions of hot rolling and annealing.
[0045] - Surface (RD-TD) observation shows that the area ratio of intermetallic compounds with a circle equivalent diameter of 0.01 μm or more is 3.0% or less The area ratio of intermetallic compounds having an equivalent circle diameter of 0.01 μm or more can be controlled to 3.0% or less by appropriately adjusting the balance of contained elements, casting speed, homogenization treatment conditions, and rolling conditions.
[0046] The ratio of MgO to MgAl2O4 in the oxide film is 4.0 or more. In order to make the abundance ratio of MgO and MgAl2O4 in the oxide film 4.0 or more, this can be achieved by subjecting the material after the final rolling to a heat treatment in an appropriate temperature range. EXAMPLES
[0047] Aluminum alloys having the composition shown in Table 1 (the balance being Al and unavoidable impurities) were prepared, and test materials were obtained through the following manufacturing process. The material was cast by the semi-continuous casting method (DC casting), and was subjected to the casting cooling rate, homogenization treatment conditions, hot rolling conditions, cold rolling conditions, and annealing shown in Table 2. Facing was performed before hot rolling. The clad material was manufactured in the same manner, and JIS A3104 was combined as the core material to prepare a test material with a clad ratio of 10%.
[0048] (Thickness of oxide film with higher atomic concentration of Mg than Al) The surface of the manufactured aluminum alloy material was subjected to elemental analysis by XPS depth profile measurement. A graph was created from the obtained data, with the vertical axis indicating atomic concentration (%) and the horizontal axis indicating sputtering time (min). The depth calculated by converting the sputtering time at which Mg2p and Al2p intersected from the material surface into SiO2 was regarded as the thickness of the oxide film where the atomic concentration of Mg is higher than that of Al.
[0049] (Area ratio of intermetallic compounds with a circle equivalent diameter of 0.01 μm or more by observation of the surface (RD-TD)) Ten secondary electron images of the surface layer of the manufactured aluminum alloy material were taken with a field emission scanning electron microscope (FE-SEM) at a magnification of ×10,000. From the taken images, the average circle equivalent diameter and area ratio of the intermetallic compounds were calculated using image analysis software, and the area ratio of intermetallic compounds with a circle equivalent diameter of 0.01 μm or more was shown.
[0050] (Ratio of MgO and MgAl2O4 in the oxide film) The surface of the aluminum alloy material was subjected to elemental analysis by XPS depth profile measurement. In addition, the Mg2p spectrum of the single crystal substrate of MgO and MgAl2O4 was measured, and the Mg2p standard energy value of each was extracted. Using the standard energy value, the Mg2p spectrum of the aluminum alloy was subjected to waveform separation, and the abundance ratio of MgO and MgAl2O4 in the oxide film, where the atomic concentration of Mg is higher than that of Al, was calculated.
[0051] (Corrosion resistance) ·Bare wood A 20 x 80 mm sample was cut from bare material with a thickness of 1 mm that had not been subjected to brazing heat treatment, and one side of the sample was masked. A cyclic spray test was carried out for 4 weeks, in which a 4.2% NaCl solution adjusted to pH 2.8-3.0 with 10 ml / L of acetic acid was sprayed at 50°C for 0.5 hours, then wetted at 50°C for 1.5 hours. After the corrosion test, the sample was immersed in a boiled phosphoric acid chromic acid mixed solution to remove the corrosion products, and the cross section was observed with an optical microscope to measure the maximum corrosion depth. The maximum corrosion depth of each bare material was evaluated on the following three levels: A, B, and C. [Evaluation Criteria] A: Maximum corrosion depth is less than 300 μm and corrosion resistance is good. B: Maximum corrosion depth is 300 μm or more and less than 500 μm, and corrosion resistance is relatively good. C: Maximum corrosion depth is 500μm or more and corrosion resistance is poor
[0052] Cladding materials A 20 x 80 mm sample was cut from the 0.2 mm thick one-sided clad material (10% clad) after brazing heat treatment, and the core side was masked. A cyclic spray test was carried out for 4 weeks, in which a 4.2% NaCl solution adjusted to pH 2.8-3.0 with 10 ml / L of acetic acid was sprayed at 50°C for 0.5 hours, then wetted at 50°C for 1.5 hours. After the corrosion test, the sample was immersed in a boiled phosphoric acid chromic acid mixed solution to remove the corrosion products, and the cross section was observed with an optical microscope to measure the maximum corrosion depth. The maximum corrosion depth of each clad material was evaluated on a three-level scale of A, B, and C as follows. [Evaluation Criteria] A: Maximum corrosion depth is less than 50 μm and corrosion resistance is good. B: Maximum corrosion depth is 50 μm or more and less than 100 μm, and corrosion resistance is relatively good. C: Maximum corrosion depth is 100μm or more and corrosion resistance is poor
[0053] [Table 1]
[0054] [Table 2]
[0055] [Table 3] [Explanation of symbols]
[0056] 1. Aluminum alloy clad material 1A Aluminum alloy clad material 2 Heartwood 3 Sacrificial anode material 3A Sacrificial Anode Material 3B Sacrificial anode material
Claims
1. The alloy has a composition containing, by mass%, 0.5 to 2.0% Mg, 0.3% or less Fe, 0.1 to 0.3% Si, with the balance being Al and unavoidable impurities, in which the Si / Fe ratio, which is the ratio of the Si content to the Fe content, by mass%, is 0.5 or more, and the Mg / Si ratio, which is the ratio of the Mg content to the Si content, by mass%, is 2.0 or more; An oxide film having a higher atomic concentration of Mg than Al is formed on the surface, the thickness of the oxide film is 20 nm or more, and the area ratio of intermetallic compounds having a circle equivalent diameter of 0.01 μm or more by observation of the surface (RD-TD) is 3.0% or less, and MgO and MgAl 2 O 4 The aluminum alloy material is characterized in that the abundance ratio of is 4.0 or more.
2. The aluminum alloy material according to claim 1, further comprising, in mass%, Zn: 0.1 to 2.0%, and an Mg / Zn ratio, which is a ratio of the Mg content to the Zn content, in mass%, is 0.3 or more.
3. The aluminum alloy material according to claim 1 or 2, characterized in that the composition further contains, by mass%, Mn: 0.1 to 0.3%.
4. 3. The aluminum alloy material according to claim 1, wherein the amount of Cu in the inevitable impurities in the composition is restricted to 0.01% or less.
5. 4. The aluminum alloy material according to claim 3, wherein the content of Cu in the inevitable impurities in the composition is restricted to 0.01% or less.
6. 3. An aluminum alloy clad material comprising the aluminum alloy according to claim 1 or 2 as a sacrificial anode material bonded to one or both sides of a core material.
7. 4. An aluminum alloy clad material comprising the aluminum alloy according to claim 3 as a sacrificial anode material bonded to one or both sides of a core material.
8. 5. An aluminum alloy clad material comprising the aluminum alloy according to claim 4 as a sacrificial anode material bonded to one or both sides of a core material.
9. 6. An aluminum alloy clad material comprising the aluminum alloy according to claim 5 as a sacrificial anode material bonded to one or both sides of a core material.
Citation Information
Patent Citations
Highly corrosion resistant aluminum clad material for heat exchanger
JP2006037137A